“We’re in the Defining Moment Where We’re Able to Figure Out What the Digital Norms are Going to Be” - Risk, Laura (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Cellist Mike Block (Silkroad Ensemble), here interviewed by Laura Risk, describes the work of moving his music camps online and the transition to teaching virtually in a conservatory setting. He discusses the challenges of learning to teach and perform online, and finding new ways to generate revenue in the digital realm.